Legacies of the Drunken Master : politics of the body in Hong Kong kung fu comedy films - White, Luke, Ph. D. (Asia pop!, 2020)
"In 1978 the films Snake in the Eagle's Shadow and Drunken Master, both starring a young Jackie Chan, caused a stir in the Hong Kong cinema industry and changed the landscape of martial arts cinema. Mixing virtuoso displays of acrobatic kung fu with knockabout humor to huge box office success, they broke the mold of the tragic and heroic martial arts film and sparked not only a wave of imitations, but also a much longer trend for kung fu comedies that continues to the present day. Legacies of the Drunken Master-the first book-length analysis of kung fu comedy-interrogates the politics of the films and their representations of the performing body. It draws on an interdisciplinary engagement with popular culture and an interrogation of the critical literature on Hong Kong and martial arts cinema to offer original readings of key films. These readings pursue the genre in terms of its carnival aesthetic, the utopias of the body it envisions, its highly stylized depictions of violence, its images of masculinity, and the registers of its "hysterical" laughter. The book's analyses are carried out amidst kung fu comedy's shifting historical contexts, including the aftermath of the 1960s radical youth movements, the rapidly globalizing colonial enclave of Hong Kong and the emerging consciousness of its 1997 handover to China, and the transnationalization of cinema audiences. It argues that through kung fu comedy's images of the body, the genre articulated in complex and often contradictory ways political realities relevant to late twentieth-century Hong Kong and the wider conditions of globalized capitalism. The kung fu comedy entwines us in a popular cultural history that stretches into the folk past and forward into utopian and dystopian possibilities"--